2009
DOI: 10.1371/journal.pone.0005210
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Staphylococcus aureus by Macrophages Exerts Cytoprotective Effects Manifested by the Upregulation of Antiapoptotic Factors

Abstract: It is becoming increasingly apparent that Staphylococcus aureus are able to survive engulfment by macrophages, and that the intracellular environment of these host cells, which is essential to innate host defenses against invading microorganisms, may in fact provide a refuge for staphylococcal survival and dissemination. Based on this, we postulated that S. aureus might induce cytoprotective mechanisms by changing gene expression profiles inside macrophages similar to obligate intracellular pathogens, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 69 publications
5
132
0
Order By: Relevance
“…rsp expression is not required for dissemination of S. aureus from the blood or for deep abscess formation, and we have identified and characterized rsp loss-of-function mutants found in human bacteremia. Thus, our data suggest that S. aureus can adopt an attenuated cytotoxic phenotype, with prolonged intracellular residence (51)(52)(53), which permits effective dissemination of the organism with few initial symptoms, followed by deep abscess establishment. The attenuated toxicity phenotype was not noted in isolates from skin and soft tissue infection (17), suggesting that such attenuated toxicity and intracellular survival may be particularly important in bloodstream infection, as opposed to other forms of infection, such as skin and soft tissue infection.…”
Section: Discussionmentioning
confidence: 74%
“…rsp expression is not required for dissemination of S. aureus from the blood or for deep abscess formation, and we have identified and characterized rsp loss-of-function mutants found in human bacteremia. Thus, our data suggest that S. aureus can adopt an attenuated cytotoxic phenotype, with prolonged intracellular residence (51)(52)(53), which permits effective dissemination of the organism with few initial symptoms, followed by deep abscess establishment. The attenuated toxicity phenotype was not noted in isolates from skin and soft tissue infection (17), suggesting that such attenuated toxicity and intracellular survival may be particularly important in bloodstream infection, as opposed to other forms of infection, such as skin and soft tissue infection.…”
Section: Discussionmentioning
confidence: 74%
“…The OPK assays followed published protocols (17,20,23), with one modification: in this study, S. aureus strains were grown overnight and in Columbia broth plus 2% NaCl (15,18,21).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that S. aureus internalized by mouse polymorphonuclear cells (PMNs) and human macrophages may survive intracellularly (16), and in the case of infected macrophages there is an increased resistance to apoptosis (17). Using a gentamicin protection assay to measure viable intracellular S. aureus cells, we found that when dilutions of antibody to CP8 were added to a constant amount of antibody to dPNAG, and vice versa, there was enhanced intracellular survival of S. aureus over that achieved with the opsonically active mixtures of single antigenic specificities (Supplemental Figure 1).…”
Section: Figurementioning
confidence: 99%
“…Microarray analysis was performed using HU133 ϩ 2 human Affymetrix GeneChips as described previously. 16 A separate GeneChip was used for each donor. Genes were defined as differentially expressed when changes in transcript levels were statistically significant by t test and/or analysis of variance as indicated, were at least 1.5-fold increased or decreased compared with cells from control subjects, and transcripts passed all quality filters.…”
Section: Microarray Analysismentioning
confidence: 99%